2018
DOI: 10.1186/s13673-018-0156-3
|View full text |Cite
|
Sign up to set email alerts
|

Facial expression recognition using optimized active regions

Abstract: Facial expression, which is a fundamental mode of transporting human's emotions, plays a significant role in our daily communication. Facial expression recognition is a complex and interesting problem, and finds its applications in driver safety, health-care, humancomputer interaction etc. Due to its wide range of applications, facial expression recognition has received substantial attention among the researchers in the area of computer vision [1-3]. Although a number of novel methodologies have been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 47 publications
(64 reference statements)
3
15
0
Order By: Relevance
“…Also, we try to use Soft-NMS (soft non-maximum suppression) to provide a dynamic regression to improve the detection accuracy of small target objects and dense objects [21]. In addition, the flexible use of multi-level convolution feature fusion [22], the addition of fine-grained feature classification [23], and a more comprehensive evaluation method for multi-object detection [24], all make multi-object detection become more efficient and accurate.…”
Section: Object Detectionmentioning
confidence: 99%
“…Also, we try to use Soft-NMS (soft non-maximum suppression) to provide a dynamic regression to improve the detection accuracy of small target objects and dense objects [21]. In addition, the flexible use of multi-level convolution feature fusion [22], the addition of fine-grained feature classification [23], and a more comprehensive evaluation method for multi-object detection [24], all make multi-object detection become more efficient and accurate.…”
Section: Object Detectionmentioning
confidence: 99%
“…For CohnKanade( CK+) database, the accuracy recorded was 95.79%. Sun et al [14] have suggested a method to search three kinds of active regions, i.e., left eye regions, right eye regions, and mouth regions. CNN is used to extract information and classify expressions.…”
Section: Related Workmentioning
confidence: 99%
“…e discriminative features are also selected from triangle and line features with the multiclass AdaBoost algorithm. Sun et al [7] proposed an effective method for the selection of optimized active face regions. ey used convolution neural network (CNN) to extract features from optimized active face regions.…”
Section: Related Workmentioning
confidence: 99%